(untitled) (TEST Ticontre. Theory Text Translation, 2020)
ABSTRACT The influence of the Greco-Latin classics and the revision of mythology in the poetry of Aurora Luque have been studied on several occasions, as well as the echoes of Luis Cernuda in her verses. Therefore, we will not study these sources: we will focus on what is halfway between the two periods, convinced that some authors of the sixteenth and seventeenth centuries constitute a fundamental link in the impact of Greek and Latin authors in the contemporary works. Of course, we consider intertextuality not only as a direct relationship of the work with its sources, but also as a resonance of the literary tradition, as an implicit presence of the canonized voices of the past. For reasons of space, we will focus on one of the possible routes, tracking the traces of the myth of Icarus that is updated in the Renaissance and in the Baroque, and affects our poet, both directly and by reading the golden and contemporary re-elaborations. After quickly reviewing Luque’s creative trajectory, from the role of the fable in her compositions, we will analyse the influences of authors such as Garcilaso de la Vega, Fernando de Herrera, Luis de Góngora, Lope de Vega, Francisco de Quevedo and the Conde de Villamediana. Our aim will be to demonstrate that the re-elaborations of the myth often attributed to Luque are based on the proposals of the named poets of the Golden Age, from whom our writer brings inspiration for her new postmodern versions.